The mechanics of soils and foundations - Atkinson, John. (London : Taylor & Francis, 2007)
Suitable for undergraduates of geotechnical engineering for civil engineers, this textbook sets out the basic theories of soil mechanics; combining both classical and critical state theories. It describes soil behaviour by relatively simple equations with clear parameters. It also includes experimental demonstrations to illustrate the principles.
Simple Experiments 1. Introduction to Geotechnical Engineering 2. Basic Mechanics 3. Essentials of Material Behaviour 4. The Structure of the Earth 5. Classification of soils 6. Pore Pressure, Effective Stress and Drainage 7. Laboratory Testing of soils 8. Compression and Swelling 9. Critical State Strength of soil 10. Peak States 11. Behaviour of soil before Failure 12. Cam Clay 13. Stiffness of soil 14. Steady State Seepag 15. Consolidation 16. Natural Soils 17. Ground Investigations 18. Soil Parameters for Design 19. Ultimate Stability of Soil Structures Using Bound Methods 20. Limit Equilibrium Method 21. Stability of Slopes 22. Bearing Capacity and Settlement of Shallow Foundations 23. Piled Foundations 24. Earth Pressure and Stability of Retaining Walls 25. Tunnelling in Soft Ground 26. Behaviour of Unsaturated Soils 27. Geotechnical Centrifuge Modeling 28. Concluding Remarks Find literature about John Atkinson share
Includes bibliographical references and index.
Keywords: Soil mechanics; Foundations; Slopes (Soil mechanics)